2018
DOI: 10.1371/journal.pone.0205008
|View full text |Cite
|
Sign up to set email alerts
|

Associations between diabetes mellitus and pulmonary hypertension in chronic respiratory disease patients

Abstract: BackgroundPulmonary hypertension (PH) is a common complication of chronic respiratory disease. Recent studies have reported diabetes mellitus (DM) to be a poor prognostic factor in patients with chronic respiratory disease, including chronic obstructive pulmonary disease or interstitial pneumoniae. However, the association between DM and PH in chronic respiratory disease remains unclear. In this study, we aimed to investigate whether DM is a predictor of PH in patients with chronic respiratory disease.MethodsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…Despite extensive adjustment for potential confounders, residual confounding cannot be fully ruled out. For example subclinical respiratory disease may be important in the association of (pre)diabetes and RA and RV structure and function [39]. Moreover, the use of body surface area to index the RA and LV mass may lead to overcorrection in the more obese (e.g.…”
Section: Confoudingmentioning
confidence: 99%
“…Despite extensive adjustment for potential confounders, residual confounding cannot be fully ruled out. For example subclinical respiratory disease may be important in the association of (pre)diabetes and RA and RV structure and function [39]. Moreover, the use of body surface area to index the RA and LV mass may lead to overcorrection in the more obese (e.g.…”
Section: Confoudingmentioning
confidence: 99%
“…Although DM affects arterial function and contributes to systemic arterial hypertension and, in particular, pulmonary hypertension [ 59 ], the effect on veins as part of diabetic vasculopathy is far from being proved. Hyperglycemia and especially fluctuating blood sugar levels seem to contribute to splanchnic hyperemia and elevated portal pressure, increasing the risk of VH [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that patients with DM are at increased risk of PH and pulmonary embolism [5,44]. It has been shown that DM is an independent factor in PH development in patients with chronic obstructive pulmonary disease and interstitial pneumonia [38,45]. The experimental data generally confirm the existence of such a relationship [17,46].…”
Section: Groupmentioning
confidence: 99%